Dual-Mode Encryption for UC-Secure String OT from Learning with Errors - Momeng Liu; Yupu Hu; Qiqi Lai; Shanshan Zhang; Huiwen Jia; Wen Gao; Baocang Wang (IET Information Security)
Universal composability (UC) is a primary security flavor for designing oblivious transfer (OT) due to its advantage of arbitrary composition. However, the study of UC-secure OT over lattices is still far behind compared with constructions over prequantum assumptions. Relying on the learning with errors (LWE) assumption, Quach proposes a dual-mode encryption scheme (SCN’20) for deriving a two-round OT whose security is provably UC-secure in the common reference string (CRS) model. Due to its use of a randomized rounding function proposed by Benhamouda et al. (PKC’18), this OT can only be limited to transmitting single-bit messages. Therefore, conducting trivial repetitions of Quach’s OT when transmitting multibit strings would be very costly. In this work, we put forward a modified dual-mode encryption cryptosystem under the decisional LWE assumption, from which we can derive a UC-secure string OT with both full-fledged dual-mode security and better efficiency on transmitting strings. The key technique we adopt is a key reconciliation scheme proposed by Jiang et al. (PKC’20), which is utilized to extend the single-bit symmetric encryption key (produced by the aforementioned rounding function) to a multibit case. Through a comprehensive performance analysis, we demonstrate that our proposal can indeed strike a balance between security and efficiency.